Plan B, a gathering of strangers (or) this is not working. - Hutton, Dean (Michaelis School of Fine Art, 2024)
The text and images that follow queers2 a dissertation submitted in fulfilment of the requirements of the award of a degree of Master of Fine Art at Michaelis School of Fine Art, as a cohort of the Institute of Creative Arts. The student explores methodologies of Self-Writing, Performance (studies) as Research; Technology as self-reflection and Radical Sharing; considers the Phenomenologies of Whiteness, embodied power and performing the transgressive white body to contribute to understandings of how the white body performs visuality, hypervisibility, reproduction3, considers its relationship to surveillance and embraces becoming monster. The design of this dissertation is an engagement with the current expectations of an object of academic enquiry – the publication bridges disciplines of Fine Art, Media and Performance studies. Treat this as a notebook, a work-in-progress, in transition – an object of research. Add your own notes, doodles and comments. Share it.